I WANT TO TALK ABOUT THE STROKES IN MUSIC - Абдурахманова Манзура Батировна (Journals Park Publishing, 2023)
Obtaining basic knowledge, skills, and abilities. Formation of a creatively oriented personality.
Keywords: innovations, repertoire, articulation, creative task, interactive methods, education.